2011
DOI: 10.1080/13691058.2011.556201
|View full text |Cite
|
Sign up to set email alerts
|

‘What does it take to be a man? What is a real man?’: ideologies of masculinity and HIV sexual risk among Black heterosexual men

Abstract: Research documents the link between traditional ideologies of masculinity and sexual risk among multi-ethnic male adolescents and White male college students, but similar research with Black heterosexual men is scarce. This exploratory study addressed this gap through six focus groups with 41 Black, low to middle income heterosexual men aged 19 to 51 years in Philadelphia, PA. Analyses highlighted two explicit ideologies of masculinity: that Black men should have sex with multiple women, often concurrently; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
132
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(139 citation statements)
references
References 62 publications
4
132
3
Order By: Relevance
“…15,32 Endorsement of these traditional masculinity norms, which may include promotion of sexual partner concurrency and negative attitudes toward same-sex attraction, has previously been associated with HIV risk behaviors in both heterosexual and gay-identified black men. [33][34][35] Higher levels of agreement with traditional masculinity beliefs are generally associated with risk behaviors such as sexual partner concurrency and inconsistent condom use. [36][37][38] Some researchers have suggested that growing up with non-resident fathers is associated with less adherence to traditional masculinity norms, 39 which might be interpreted as portending lower sexual risk.…”
Section: Masculine Socializationmentioning
confidence: 99%
“…15,32 Endorsement of these traditional masculinity norms, which may include promotion of sexual partner concurrency and negative attitudes toward same-sex attraction, has previously been associated with HIV risk behaviors in both heterosexual and gay-identified black men. [33][34][35] Higher levels of agreement with traditional masculinity beliefs are generally associated with risk behaviors such as sexual partner concurrency and inconsistent condom use. [36][37][38] Some researchers have suggested that growing up with non-resident fathers is associated with less adherence to traditional masculinity norms, 39 which might be interpreted as portending lower sexual risk.…”
Section: Masculine Socializationmentioning
confidence: 99%
“…16,17 In addition, negative attitudes toward homosexuality and a rejection of effeminate behavior are defining components of traditional ideologies of masculinity in the black community. 18 In 24 MSDH invited the Centers for Disease Control and Prevention (CDC) to collaborate in an investigation to understand risks for HIV infection among young black MSM in Mississippi.…”
Section: Introductionmentioning
confidence: 99%
“…Although college students have traditionally been considered a low-risk group for HIV, African American/black university students tend to have profound misconceptions about HIV exposure and transmission and may be at risk [8,16,[33][34][35][36][37].…”
Section: Navigating College Masculinity and Sexual Identitymentioning
confidence: 99%
“…A paucity of HIV prevention strategies have been demonstrated to be efficacious and effective for African American/black heterosexual men, particularly those of college age [8][9][10][11][12][13].…”
Section: Gaps In Prevention Sciencementioning
confidence: 99%